Food Flavorings,Colorings and Preservatives: A Chef's Guide - Newman,Manuel (.-USA :States Academic Press, 2023)
Most of the topics covered herein address the modern trends in food preparation, stylization and preservation. It will prove to be an important reference text to students, chefs and anyone else with a passion for cooking.
Keywords: Cooks,Flavoring essences,Coloring matter in food,Food preservatives -Vocational guidance